Legal Protection for Victims of Domestic Violence - Rospita Adelina Siregar; Endah Labati Silapurna; Wilnan Fatahillah; Oktaviana Hardayanti Adismana; Wahab Aznul Hidaya (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Domestic violence is any action that causes suffering or misery in the form of domestic violence, whether physical, sexual, psychological, or neglect of someone, especially women, within the household, victims of domestic violence are those who have a social position or status. the weak, which makes someone a victim, especially women and children. The method used in this research is a normative juridical legal research approach which then results in the conclusion that perpetrators of domestic violence will receive legal consequences in accordance with their motives for violence as explained in the Law on the Elimination of Domestic Violence, while the victims receive protection. their rights include protection from family, law enforcement agencies, social institutions, medical needs, confidentiality, legal assistance and assistance as well as spiritual guidance services